2015
DOI: 10.1016/j.arabjc.2011.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Plasma treatment by gliding arc discharge of dyes/dye mixtures in the presence of inorganic salts

Abstract: The gliding arc discharge plasma (GAD) technique was used for discoloration and degradation of an anthraquinone dye Alizarin red S (ARS), an azo dye Orange G (OG) and their mixture. The influence of chloride and sulfate salts on the efficiency of treatment has also been studied. The aim of this study is the discoloration and degradation by GAD of ARS, and OG and their mixture.The GAD plasma generated between two moist air metallic electrodes connected to a high voltage produced chemical species and highly reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…In these situations Gliding Arc discharges seems to be suitable alternative providing similar advantages as the microwave plasma, moreover with lower costs for the acquisition of the equipment. Gliding Arc discharges are being recently utilized for decontamination of water and air [1,2], degradation of various compounds [3][4][5][6] modification of surface properties of solid materials [7][8][9] or production of hydrogen [10]. The large number of applications of gliding arc is possible due to the nonequilibrium character of this kind of plasma discharge, which consequently enables to produce relatively high number of charged and highly reactive particles.…”
Section: Introductionmentioning
confidence: 99%
“…In these situations Gliding Arc discharges seems to be suitable alternative providing similar advantages as the microwave plasma, moreover with lower costs for the acquisition of the equipment. Gliding Arc discharges are being recently utilized for decontamination of water and air [1,2], degradation of various compounds [3][4][5][6] modification of surface properties of solid materials [7][8][9] or production of hydrogen [10]. The large number of applications of gliding arc is possible due to the nonequilibrium character of this kind of plasma discharge, which consequently enables to produce relatively high number of charged and highly reactive particles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the SP was utilized as an assistant for decomposition of organic pollutants. Recently, plasmaassisted water treatments, including thermal/nonthermal plasma, microwave plasma, or arc plasma [21][22][23], have been demonstrated to be the effective way for remediation of waste water. Plasma-based techniques could oxidize and decompose the toxic organic molecules to less toxic or nontoxic small by-products.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are some references regarding the application of nonthermal plasmas to a mixture of the organic dyes [39][40][41][42]. In [42], it was found that the destruction of two dyes occurs faster in their mixture than in the solutions, which contain only one dye. It was assumed that the dyes in a mixture or its byproducts could be a catalyst in the degradation process.…”
Section: Introductionmentioning
confidence: 99%